Diagnostic Symptoms of Corona Audible Noise in Continuous Monitoring Systems - WSZOŁEK, Tadeusz (Archives of Acoustics, 2011)
Random nature of corona processes in UHV power lines and the accompanying noise is the reason that in practice the best determination of acoustic parameters, necessary for the noise evaluation, is obtained from the continuous monitoring procedure. However because of considerable fluctuations (both the useful signal part and the interfering components), careful selection of monitored parameters is necessary to enable a possibility of automatic determination of the parameters that are required for long-term evaluation of corona noise. In the present work a practical realization is shown for estimation of corona noise parameters, based on the data obtained from continuous monitoring stations, making use of the statistical spectra measurement and characteristic features of corona process acoustic signal. Selected results are presented from continuous monitoring of corona noise generated at a 400 kV power line, with special attention focused on definitions of the measured quantities, which enable automatic estimation of the basic factors required for noise evaluation. Accompanying monitoring of environmental conditions, including humidity, precipitation intensity and fog density, that are well correlated with the corona process intensity, which might definitely increase the filtration efficiency of environmental disturbances and on the other hand, it enables verification of calculation methods applied to corona noise. The paper also contains a description of practical approach to selection signal parameters of corona noise in continuous monitoring stations.